O gênero charge como ensino aprendizagem - SILVA, Renata Medeiros (2023)
The present work will have as its central proposal to know a little about the textual genres, what is their importance in the degree and to bring aspects of their pedagogical practices. A proposal will be worked through the cartoon genre with the political theme of the year 2022, taking into account its role in the teaching-learning context aimed at students of the 7th year of elementary school II. Throughout the text, it will be shown in the case of cartoons that one of the requirements is textual interpretation, as it requires a lot of knowledge not only about the policy that will be the topic addressed, but also historical, geographic and language facts. The cartoon is a humorous, informative and opinionated instrument of extreme importance for the formation of critical and reflective students, in this conception, the cartoon genre has contributed to the achievement of this objective, because with the application of the genre in the classroom, the student began to better understand the function of the text.